ECHOING WASATHIYYAH: HOW INDONESIA EMERGESTHE NORM OF MODERATE ISLAM IN INTERNATIONAL DISCOURSE - Ahmad Asrul Azwar Irfan; Sheila Shafira Mahsyar (International Conference on Social and Islamic Studies, 2021)
The rise of negative discourse in the consequences of 9/11 put a strong pressure onMuslim-majority countries. The norm of terrorism or extremism is often attached to theidea of jihad which adhered to Islam. The implication of these diffusion is actually forcingmany actors to restore Islam ideas that are not related to terrorism or extremism. ModerateIslam as an alternative norm finally tried to restore the previously diffused norm of Islam.Moderate Islam is then widely echoed in many countries. One of them is Indonesia, whichhas a Muslim-majority population. In this study, the researchers took the related literaturesthat describe, firstly, how far the norm of moderate Islam were raised in internationaldiscourse and then how far Indonesia was able to emerge the norm. Therefore, theresearchers used a qualitative descriptive method. From the results of the study, theresearchers noted that there were dynamic results in emerging the norm of moderateIslam, Especially in Indonesia. The norm emergence of Wasathiyyah which contained inthe norm of moderate Islam is considered to have succeed involving many communitygroups and government institutions in solidarity to emerge Wasathiyyah. The dynamics ofemerging this norms in Indonesia cannot be separated from both domestic andinternational incentives. The researchers concluded that the norm of moderate Islam hasreached a tipping point in international discourse which of course cannot be shatteredfrom the influence of Muslim-majority countries such as Indonesia, despite the emergenceof this norms was contested by extremism norm in the restoration of Islam norms. Thus,the researchers advocated for urging more actors, motives, and mechanisms to carry outthe norm so that it can be absolutely legitimized in the international discourse.